Handbook of research on latin american and caribbean international relations : the development of concepts and themes - Atkins, G. Pope. ([S.l.] : Westview Press, 2001)
The study of Latin American and Caribbean international relations has a long evolution both within the development of international relations as a general academic undertaking and in terms of the particular characteristics that distinguish the approaches taken by scholars in the field. This handbook provides a thorough multidisciplinary reference guide to the literature on the various elements of the international relations of Latin America and the Caribbean. Citing over 1600 sources that date from the nineteenth century to the present, with emphasis on recent decades, the volume's analytic essays trace the evolution of research in terms of concepts, issues, and themes. The Handbook is a companion volume to Atkins' Latin America and the Caribbean in the International System, Fourth Edition, but also serves as an invaluable stand-alone reference volume for students, scholars, researchers, journalists, and practitioners, both official and private.
Keywords: Caribbean Area; International relations; Latin America